Competency-Based Performance Evaluation Strategies in Combat Units of the Main Command within the Indonesian National Armed Forces (TNI) - Tresna Kusumawati (PT. Anagata Sembagi Education, 2026)
This study examines competency-based performance evaluation strategies applied to combat units under the Main Command (Komando Utama) structures within the Indonesian National Armed Forces (TNI). Traditional military appraisal systems in Indonesia have historically relied on seniority, administrative compliance, and generic rating scales that inadequately capture the operational competencies required of modern combat readiness. Using a qualitative descriptive research design with a case study approach, this study explores how competency frameworks covering technical-tactical proficiency, physical readiness, leadership under operational stress, discipline and character, and teamwork are conceptualized, implemented, and perceived within combat units. Data were gathered through semi-structured interviews with commanders and staff officers, document analysis of unit evaluation records, and field observation, then triangulated and analyzed thematically. Findings indicate that although formal competency indicators exist, their application remains fragmented, subject to inconsistent interpretation across units, and weakly integrated with career development and readiness planning. The study identifies four strategic levers for strengthening competency-based evaluation: standardized multi-source assessment instruments, digital performance dashboards, competency-linked career pathways, and periodic joint-command calibration forums. This research contributes a context-specific competency evaluation model for TNI combat units, addressing a novelty gap in existing literature that has predominantly examined competency and performance separately or focused on non-combat administrative personnel rather than operational combat readiness.